The Colonial and Modernization Projects of the Omanis in Zanzibar, 1837-1885 : Recreating the Caribbean, Muscat, Bombay, or Cairo in East Africa? - Belhacel, Abdelhakim (Projects and Utopias in the Age of Empires and Global Revolution (late 18th - Late 19th Century), 2025)
Keywords: Vie politique -- Zanzibar -- 1806-1856

The three voyages of Black Eagle: Piracy, transnationality and the first French East India Company’s flagship - Belhacel, Abdelhakim (International Journal of Maritime History, 2025)
This article explores the story of the French East India Company’s first flagship, originally a Dutch-built privateer vessel, from its inception in the 1660s through three significant voyages. Through an analysis of travel accounts, archival documents and secondary literature, the study explores how the ship’s transformation into a symbol of French ambition reflects the broader struggles of France’s imperial ventures under Louis XIV. Initially named Black Eagle and infamous for piracy, the vessel was repurposed as Saint-Paul and served in the nascent French East India Company. Its voyages highlight challenges such as disease, lack of maritime expertise and strained resources, which hindered the Company. By examining the ship’s role, this article sheds light on the transnational networks, political rivalries and economic aspirations that shaped France’s entry into the Indian Ocean trade. The study highlights the relationship between a ship’s tumultuous history and the French East India Company’s strategic ambitions and transnational entanglements.
Keywords: Commerce -- France

Un projet d’alliance entre Kilwa et la France contre l’expansionnisme omanais, étude d’une lettre en arabe de mfalme Sulaymān b. Ḥasan à Louis XVIII - Belhacel, Abdelhakim; Qaisi, Fu’ad al- (Afriques. Débats, méthodes et terrains d’histoire, 2025)
La série « Réunion » des Archives nationales d’outre-mer conserve plusieurs lettres en arabe issues des correspondances entre les Français et les souverains musulmans d’Afrique de l’Est. L’une d’elles, écrite en 1819, est traduite en français et éditée pour la première fois. Son étude apporte un éclairage crucial sur la nature des relations entre Swahili, Omanais et Français au début du xixe siècle. Elle fait apparaître l’importance des réseaux négriers pour la diplomatie française et leur persistance après l’abolition officielle de la traite. Elle permet également de comprendre comment le sultanat de Kilwa tente de se défaire de la mainmise omanaise. De plus, elle montre l’importance de l’emploi de la langue arabe pour les correspondances diplomatiques dans l’océan Indien. La lettre de mfalme Sulaymān b. Ḥasan à Louis XVIII vise en effet à sceller une alliance entre la France et le sultanat de Kilwa contre les Omanais installés à Zanzibar, grâce aux bons offices d’un arabisant et d’un négrier. L’étude de ce document comprend une reproduction et une analyse de la lettre et de son enveloppe, une retranscription, une traduction et une analyse permettant de comprendre le contexte (acteurs, situation politique) et de dégager ses apports quant à la connaissance des stratégies de résistance des souverains swahili face à l’expansionnisme omanais en Afrique de l’Est.
Keywords: Relations -- Zanzibar -- Qilwa; Vie politique -- Zanzibar -- 1806-1856